Research on VoNR voice wireless optimization strategy - Xinchao ZANG; Ronglin LI (Dianxin kexue)
There are two 5G voice solutions, EPS Fallback and VoNR.In the early stage of 5G network construction, 5G base station coverage rate and terminal penetration rate were not high, so EPS Fallback was used as a 5G voice transition solution.At present, with the deployment of 2.6 GHz and 700 MHz networks, the SA network achieves independent networking, and VoNR will be the main solution for 5G voice.In order to actively respond to the deployment of VoNR and analyze the advantages of VoNR from multiple dimensions, an in-depth research on VoNR features, parameters, and application scenarios were conducted, VoNR wireless strategy deployment was formulated, for uplink weak field, interference, large traffic characteristics of all kinds of scenarios functions such as deployment and optimization to provide suggestion and scheme, and prepares for VoNR’s official commercial use.